Development of a novel handheld intra-operative laparoscopic Compton camera for 18F-Fluoro-2-deoxy-2-D-glucose-guided surgery. (18th July 2016) - Nakamura, Y; Shimazoe, K; Takahashi, H; Yoshimura, S; Seto, Y; Kato, S; Takahashi, M; Momose, T
Abstract: As well as pre-operative roadmapping by 18 F-Fluoro-2-deoxy-2-D-glucose (FDG) positron emission tomography, intra-operative localization of the tracer is important to identify local margins for less-invasive surgery, especially FDG-guided surgery. The objective of this paper is to develop a laparoscopic Compton camera and system aimed at use for intra-operative FDG imaging for accurate and less-invasive dissections. The laparoscopic Compton camera consists of four layers of a 12-pixel cross-shaped array of GFAG crystals ( 2 × 2 × 3 mm 3 ) and through silicon via multi-pixel photon counters and dedicated individual readout electronics based on a dynamic time-over-threshold method. Experimental results yielded a spatial resolution of 4 mm (FWHM) for a 10 mm working distance and an absolute detection efficiency of 0.11 cps kBq −1, corresponding to an intrinsic detection efficiency of ∼0.18%. In an experiment using a NEMA-like well-shaped FDG phantom, a ϕ 5 × 10 mm cylindrical hot spot was clearly obtained even in the presence of a background distribution surrounding the Compton camera and the hot spot. We successfully obtained reconstructed images of a resected lymph node and primary tumor ex vivo after FDG administration to a patient having esophageal cancer. These performance characteristics indicate a new possibility of FDG-directed surgery by using a Compton camera intra-operatively.